Pathology of the Gastrointestinal Tract - Carneiro, Fátima; Chaves, Paula; Ensari, Arzu (Springer International Publishing : Imprint: Springer, 2017)
This book covers the complete field of the pathology of the Gastrointestinal tract - from Abetalipoproteinemia to Zollinger-Ellison Syndrome. The alphabetically arranged entries, each of which provides a detailed description of a specific pathological disease pattern, allow readers to quickly and easily find the information they need.
Keywords: Medicine.; Gastroenterology.; Pathology.; elektronické knihy; electronic books